Pemenuhan Hak Kesehatan Reproduksi: Kajian Pengalaman Pekerja Perempuan di Perusahaan Tekstil dan Garmen di Sukoharjo - Pandan Wangi Sukma Listyono Putri; Sri Hilmi Pujihartati (Universitas Sebelas Maret (UNS), 2024)
Reproductive health rights are among the rights of women guaranteed by the government through laws and various other regulations, including reproductive health rights for female workers. Specifically, regulations regarding the fulfillment of reproductive health rights for female workers are written in Law Number 13 of 2003, Ministry of Health Regulation Number 15 of 2013, Ministry of Manpower Regulation No. 03/Men/1989, and CEDAW Article 11 Paragraph 1. The purpose of this research is to understand the experiences of female workers in exercising their reproductive health rights and to determine whether discrimination against female workers is still present. This study employs the Harvard Gender Analysis framework, hoping this theory can assist the author in analyzing the ease with which female workers access their reproductive health rights. The research method used is qualitative, involving in-depth interviews and observations within textile and garment companies located in Sukoharjo, using a case study approach. The results of this study indicate that, broadly speaking, female workers in textile and garment companies in Sukoharjo can easily access reproductive health rights. However, there are still some reproductive health rights that companies have not fulfilled, such as the right to menstrual leave on the second day and working hours rights.Keywords: reproductive health, female workers, discrimination, harvard